PENGARUH KEPEMIMPINAN, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA KARYAWAN AGNICOM PADANG PARIAMAN - Agus Nurofik; Sartika Yuliana (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the effect of leadership, workload and work environment on the work motivation of employees of AgniCom Padang Pariaman employees. The method used in this research is quantitative research with survey and descriptive approach. The population in this study were employees of AgniCom Padang Pariaman. The sample used is 48 people using saturated sampling technique. The data analysis technique used is multiple linear regression. The results showed that: (1) Leadership has a positive and significant effect on employee work motivation, (2) Workload has a negative and significant effect on work motivation, (3) Work environment has a positive and significant effect on employee motivation.